Mechanisms of change for a family intervention in Kenya: An Integrated Clinical and Implementation Mapping approach. (December 2022) - Giusto, Ali; Friis-Healy, Elsa A.; Kaiser, Bonnie N.; Ayuku, David; Rono, Wilter; Puffer, Eve S.
Abstract: To increase cultural relevance and maximize access for historically underserved populations, there is a need to explore mechanisms underlying treatment outcomes during piloting. We developed a mixed-method approach, Integrated Clinical and Implementation Mapping (ICIM), to explore clinical and implementation mechanisms to inform improvements in content and delivery. We applied ICIM in a pilot of Tuko Pamoja, a lay counselor-delivered family intervention in Kenya (10 families with adolescents ages 12–17). ICIM is a 3-phase process to triangulate data sources to analyze how and why change occurs within individual cases and across cases. We synthesized data from session and supervision transcripts, fidelity and clinical skills ratings, surveys, and interviews. Outputs included a comprehensive narrative and visual map depicting how content and implementation factors influenced change. For Tuko Pamoja, ICIM results showed common presenting problems, including financial strain and caregivers' distress, triggering negative interactions and adolescent distress. ICIM demonstrated that active treatment ingredients included communication skills and facilitated, prescribed time together. Families improved communication, empathy, and hope, facilitated improved family functioning and mental health. Key implementation mechanisms included provider clinical competencies, alliance-building, treatment-aligned adaptations, and consistent attendance. Results guided manual and training refinements and generated hypotheses about mechanisms to test in larger trials. Highlights: Mixed methods are an underused to explore mechanisms of change. Exploring clinical and implementation change mechanisms early can inform tailoring for cultural relevance and accessibility. Integrated Clinical and Implementation Mapping (ICIM) is a novel mixed-method approach for understanding dual mechanisms. ICIM was applied to a pilot study of a task-shared family therapy in Kenya. Active treatment ingredients and counselor abilities changed family interactions which improved family and mental health.